New clues arising from hunt of saccharides binding to galectin 3 via 3D QSAR and docking studies. (2020) - Sethi, Aaftaab; Sanam, Swetha; Alvala, Mallika
Abstract: Galectin-3 is a carbohydrate-binding protein that plays a crucial role in cancer and fibrosis. Its inhibitors have largely evolved from naturally occurring saccharides to many synthetic forms with significantly improved affinity. However, there haven't been any substantial and sizeable structure-activity relationship studies in order to develop potent and selective inhibitors. This study presents an extensively curated first of its kind dualfield-based 3D-QSAR model which sheds light on development of novel galectin-3 mono and disaccharide-based inhibitors. Training and validation of QSAR predictive models A and B were performed on a master dataset consisting of 324 compounds and 52 compounds respectively. The molecular structures and binding affinities of the compounds were acquired from literature. The binding mode of the inhibitors was explored by molecular docking. The results indicated that aryl flanking groups linked to the pyranose ring at C1 and C3 substantially improved the potency of molecules. Amino acid residues such as Arg144, His158, Arg162, Asn174, Trp181, Glu184 and Arg186 were found to be critical for binding to galectin-3. This study serves as a guideline for the design of novel, synthetically feasible, membrane-permeable and potent galectin-3 selective inhibitors. Graphical abstract: Image 1